Growth of human tumor cell lines in transferrin-free, low-iron medium - Neumannova, V; Richardson, D R; Kriegerbeckova, K; Kovar, J (In vitro cellular & developmental biology. Animal, 1995)
Iron is essential for tumor cell growth. Previous studies have demonstrated that apart from transferrin-bound iron uptake, mammalian cells also possess a transport system capable of efficiently obtaining iron from small molecular weight iron chelates (Sturrock et al., 1990). In the present study, we have examined the ability of tumor cells to grow in the presence of low molecular weight iron chelates of citrate. In chemically defined serum-free medium, most human tumor cell lines required either transferrin (5 micrograms/ml) or a higher concentration of ferric citrate (500 microM) as an iron source. However, we have also found that from 13 human cell lines tested, 4 were capable of long-term growth in transferrin-free medium with a substantially lower concentration of ferric citrate (5 microM). When grown in medium containing transferrin, both regular and low-iron dependent cell lines use transferrin-bound iron. Growth of both cell types in transferrin medium was inhibited to a certain degree by monoclonal antibody 42/6, which specifically blocks the binding of transferrin to the transferrin receptor. On the contrary, growth of low-iron dependent cell lines in transferrin-free, low-iron medium (5 microM ferric citrate) could not be inhibited by monoclonal antibody 42/6. Furthermore, no autocrine production of transferrin was observed. Low-iron dependent cell lines still remain sensitive to iron depletion as the iron(III) chelator, desferrioxamine, inhibited their growth. We conclude that low-iron dependent tumor cells in transferrin-free, low-iron medium may employ a previously unknown mechanism for uptake of non-transferrin-bound iron that allows them to efficiently use low concentrations of ferric citrate as an iron source. The results are discussed in the context of alternative iron uptake mechanisms to the well-characterized receptor-mediated endocytosis process.
Keywords: železité sloučeniny; železo; nádorové buňky kultivované; kultivační média; chelátory; transferin; Ferric Compounds; Transferrin; Cell Culture Techniques; HeLa buňky; Humans; Iron; lidé; HeLa Cells; Tumor Cells, Cultured; Chelating Agents; Culture Media; buněčné kultury